The Oxford dictionary of modern slang - John Ayto (Oxford Univ. Press, 1993)
The book is a comprehensive and entertaining collection of slang words and phrases from throughout the English-speaking world. It presenrs over 5,000 slang words and phrases, thousands of illustrative quotations - from John Lennon to Woody Allen, full information for each entry - definitions, origins, and the date of the first use print